A Multicenter, Comparative Study of Two Pressure-Redistribution Mattresses with Repositioning Intervals for Critical Care Patients. (March 2020) - Jiang, Qixia; Liu, Yuxiu; Yu, Hui; Song, Siping; Li, Guohong; Liu, Haiying; Zhou, Yi; Zhu, Yajun; Jia, Jing; Huang, Yunjuan; Wang, Jiandong
ABSTRACT: OBJECTIVE: To compare the effectiveness of two protocols for preventing pressure injuries (PIs) in Chinese hospitals. DESIGN AND SETTING: A multicenter, open-label, comparative study conducted in seven Chinese acute care hospitals. PATIENTS AND INTERVENTION: In total, 1, 654 eligible patients were identified, and 1, 204 were enrolled in the study. Enrolled patients were randomly assigned into the trial group (4-hour repositioning combined with a viscoelastic foam mattress; n = 602) or the control group (2-hour repositioning combined with a powered air pressure redistribution mattress; n = 602). Participants received their respective protocols until they were discharged, died, or for at least 7 days. MAIN OUTCOME MEASURES: The incidence of PIs, Braden Scale scores, and the time to development of PIs. MAIN RESULTS: Ultimately, 596 trial group patients and 598 control group patients were analyzed. Thirteen patients had single new stage 2 or worse PIs. The total incidence of PIs was 1.1%. The difference between the two groups was significant (0.3% vs 1.8%). However, the difference between the groups' Braden Scale score median during the intervention was not significant (13 vs 13.5). CONCLUSIONS: The 4-hour repositioning interval combined with a viscoelastic foam mattress did not increase PI incidence or risk. These findings could help providers select the right pressure redistribution mattresses and repositioning intervals for critical care patients.